A evolução da mortalidade por causas externas no Brasil de 2006 a 2012 - Ortiz, Dennys Ghenry Samillan (2014)
External causes are the leading cause of death worldwide and the third leading cause of death in Brazil. The aim of the present study was to analyze the evolution of mortality from external causes in Brazil from 2006 to 2012. Mortality from external causes was analyzed according to age, sex, place of residence and year of occurrence, using database obtained from the Mortality Information System (SIM) and the Brazilian Institute of Geography and Statistics (IBGE). The results show anincrease of 14.1% in mortality rate from external causes during the study period, from 68.7 deaths/100,000 in 2006 to 78.4 deaths/ 100,000 in 2012. Young adults 20-29 years of age were the most affected by external causes (27,3%). Among the specific causes, homicides experienced an increase during the study period, from 26.6 deaths/100,000 in 2006 to 29.4 deaths/100,000 in 2012. This means an increase of 10.5% in the mortality rate from homicides. There was an increase in traffic accidents, from 19.9 deaths/100,000 in 2006 to 23.7 deaths/100,000 in 2012, which constitutes an increase of 19.0 % in the mortality rate from traffic accidents, being the most important one motorcycle accidents, where there was an increase of 67.8 % in the mortality rate. There was an increase in suicides during the study period, from 4.6 deaths/100,000 in 2006 to 5.3 deaths/100,000 in 2012, which means an increase of 15.0 % in the mortality rate being the South and Midwest regions the ones with the highest rates. In regard to falls, there was an increase during the study period, from 4.2 deaths/100,000 in 2006 to 6.0 deaths/100,000 in 2012, which represents an increase of 41.9% in the mortality rate from falls. The results showed that between 2006 and 2012 in Brazil there was an increase in the mortality rate for all types of causes. The largest increase in the mortality rate was due to traffic accidents, in which the accidents with motorcycles stood out. However, the largest number of deaths from external causes remains homicide, following the trend of previous periods.